2020
DOI: 10.3390/molecules25010183
|View full text |Cite
|
Sign up to set email alerts
|

Lignans and Their Derivatives from Plants as Antivirals

Abstract: Lignans are widely produced by various plant species; they are a class of natural products that share structural similarity. They usually contain a core scaffold that is formed by two or more phenylpropanoid units. Lignans possess diverse pharmacological properties, including their antiviral activities that have been reported in recent years. This review discusses the distribution of lignans in nature according to their structural classification, and it provides a comprehensive summary of their antiviral activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 89 publications
(111 reference statements)
0
70
0
Order By: Relevance
“…Similar to many other polyphenolic compounds in plants, lignans are reported to have an ecological role in helping plants to cope with biotic and abiotic stresses during growth and development [ 3 , 184 ]. Some of them are considered pharmacologically interesting due to their antiviral, antibacterial, antioxidant, and antitumor properties [ 185 ]. Due to their structure, lignans are effective antioxidants, and they have the potential to scavenge a harmful ROS that is usually overaccumulated under stress conditions.…”
Section: Lignansmentioning
confidence: 99%
“…Similar to many other polyphenolic compounds in plants, lignans are reported to have an ecological role in helping plants to cope with biotic and abiotic stresses during growth and development [ 3 , 184 ]. Some of them are considered pharmacologically interesting due to their antiviral, antibacterial, antioxidant, and antitumor properties [ 185 ]. Due to their structure, lignans are effective antioxidants, and they have the potential to scavenge a harmful ROS that is usually overaccumulated under stress conditions.…”
Section: Lignansmentioning
confidence: 99%
“…Curcumin, a component of turmeric (Curcuma longa) has been described to have several functions in preventing or treating diseases, including cancers and viral infections [49]. It has also been demonstrated that curcumin is an antiviral compound, with activity against diverse viruses such as dengue virus (serotype 2) [50], herpes simplex virus [51], human immunodeficiency virus [52], Zika and Chikungunya [53] among others. Curcumin and its analogues have proved to be useful as HIV-1 integrase inhibitor [51,54].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that curcumin is an antiviral compound, with activity against diverse viruses such as dengue virus (serotype 2) [50], herpes simplex virus [51], human immunodeficiency virus [52], Zika and Chikungunya [53] among others. Curcumin and its analogues have proved to be useful as HIV-1 integrase inhibitor [51,54]. Aloe BarbadensisAloe Vera) has been used medicinally for several thousands of years in many cultures; from ancient Egypt, Greece, and…”
Section: Introductionmentioning
confidence: 99%
“…Lignans are natural products characterized by a phenylpropanoid core (C 6 C 3 unit). Structurally, they are composed of two or more phenylpropanoid units as a basic scaffold [26][27][28]. Compounds 1, 4, and 5 are classified as phenylpropanoids, which contain a planar methylenedioxyphenyl moiety with allyl group [28].…”
Section: Isolation and Identification Of Compounds From P Pellucida mentioning
confidence: 99%